CINTA DALAM PERSPEKTIF NEUROBIOLOGI - Lina Kamelia, Oka Adnyana (Neurona Majalah Kedokteran Neuro Sains, 2012)
INTRODUCTION LOVE IS ONE OF BASIC HUMAN EMOTIONS EXPLAINS AN ATTACHMENT BETWEEN TWO INDIVIDUALS WITH A COMPLEX PROCESS VARIOUS ANATOMICAL SUBSTRATES AND NEUROPHYSIOLOGICAL PATHWAYS HAVE BEEN PROPOSED AS BASIC COMPONENTS TO DESCRIBE THE EMOTION OF LOVE IN NEUROBIOLOGY PERSPECTIVE